The Roots of African Xenophobia: A Critical Comparison of Economic, Political, and Postcolonial Explanations - Bakoji Babangida (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
One of the most topical and debated issues facing Africa today is xenophobia. Africa has not always been divided, as pre-colonial history on the continent was characterised by high levels of mobility, trade and intercultural exchange. The events of recent decades reveal the manifestation of a series of violent incidents against migrants and "non-indigenes" in South Africa, Côte d'Ivoire, Nigeria and Tunisia, driven by xenophobic undertones. This paper considers three different explanations for this phenomenon and critically examines them within competing theoretical arguments, such as economic competition theory, political manipulation theory, and the internalisation of colonial forms of othering. The paper draws on literature from social identity, relative deprivation, elite instrumentalism, and postcolonialism as well as comparative historical evidence from the last four attacks in South Africa (2008/2015/2019/2022) and the expulsions of sub-Saharan migrants in Tunisia in 2023, arguing none of these theories are independently adequate. As a result, the paper proposes a new integrative model known as the Colonial Substrate-Activation Model (CSAM). CSAM reveals that colonial othering serves as the template, economic insecurity acts as the energy source, and political manipulation functions as the catalyst for xenophobic violence. The paper concludes with pointing out methodological problems and gaps in the literature and with drawing out policy implications from the analysis of xenophobia as a problem of the structure and not only of the situation.